5(6x-7)=6(5x-6)

Simple and best practice solution for 5(6x-7)=6(5x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6x-7)=6(5x-6) equation:



5(6x-7)=6(5x-6)
We move all terms to the left:
5(6x-7)-(6(5x-6))=0
We multiply parentheses
30x-(6(5x-6))-35=0
We calculate terms in parentheses: -(6(5x-6)), so:
6(5x-6)
We multiply parentheses
30x-36
Back to the equation:
-(30x-36)
We get rid of parentheses
30x-30x+36-35=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation

See similar equations:

| 4/m=m/9 | | 7/9x+2=5/6 | | -4x-8x=75 | | 8p-56=9p-90 | | -2(3x-3-4(-2x+1)=14 | | 5n+4-3n=-2 | | -4(7+4r)=8(-2r+2) | | -3t^2+12t-9=0 | | 2x+1-3(-3.x)=56±x/16 | | 15×6=(x-2)÷3 | | X(x-32)=180 | | 62=-1+7x | | G(x)=x2-5 | | 1/t=5/t+1 | | x-3=-2/7(14) | | -24=5(8-2r)+2(r-8) | | f(3)=45×3^2-26^3-8 | | 3x+24=2x+31 | | -14=3x-5 | | -30=4(x-7)-2x | | 5.88=3(p+0.75) | | 5.88=3(p-0.75) | | 39/32=11/16-1/4x | | 3((x/2)-7)=-4 | | x=5/(-5/3) | | 446.16=220+0.88x | | 10.8-3.7x=142 | | 5.88=3p+.75 | | −16x=−14-16x=-14 | | 8x=6(x+17) | | 5.88=3p-0.75 | | -11=2/5b-5 |

Equations solver categories